2011
DOI: 10.1038/ncomms1221
|View full text |Cite
|
Sign up to set email alerts
|

Electrically controllable spontaneous magnetism in nanoscale mixed phase multiferroics

Abstract: magnetoelectrics and multiferroics present exciting opportunities for electric-field control of magnetism. However, there are few room-temperature ferromagnetic-ferroelectrics. Among the various types of multiferroics the bismuth ferrite system has received much attention primarily because both the ferroelectric and the antiferromagnetic orders are quite robust at room temperature. Here we demonstrate the emergence of an enhanced spontaneous magnetization in a strain-driven rhombohedral and super-tetragonal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
154
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(160 citation statements)
references
References 24 publications
6
154
0
Order By: Relevance
“…In specific, the Fe peak is centred at 710.8 eV, in good agreement with the expected value of 711 eV for Fe 3 þ , suggesting phase purity and a low-enough level of oxygen vacancies that they were not detected via XPS 40 . These data thus provide good evidence that the high M s values reported below do not arise from oxygen vacancies, as seen in some other sol-gel-derived materials, but more likely stem from strain effects, in closer analogy to epitaxial BFO systems 22,23,25 .…”
Section: Structural Characterizationsupporting
confidence: 54%
See 3 more Smart Citations
“…In specific, the Fe peak is centred at 710.8 eV, in good agreement with the expected value of 711 eV for Fe 3 þ , suggesting phase purity and a low-enough level of oxygen vacancies that they were not detected via XPS 40 . These data thus provide good evidence that the high M s values reported below do not arise from oxygen vacancies, as seen in some other sol-gel-derived materials, but more likely stem from strain effects, in closer analogy to epitaxial BFO systems 22,23,25 .…”
Section: Structural Characterizationsupporting
confidence: 54%
“…We also note that the low M s values in all unpoled samples preclude the possibility that iron oxide impurities or oxygen vacancies, as discussed above, from the sol-gel synthesis are the source of the high magnetization in poled samples. These M s values for electrically poled mesoporous BFO films demonstrate the highest values recorded for BFO films to date, greater even than values ranging from 0.2-0.5 m b per Fe reported in epitaxially strained BFO thin films 23,25 . Indeed, this magnetization change corresponds to a magnetoelectric coupling constant a ¼ m 0 DM/ E ¼ 1 Â 10 À 5 sm À 1 , which is on par with composite systems and much larger than that expected for single phase materials 42,43 .…”
Section: Structural Characterizationmentioning
confidence: 90%
See 2 more Smart Citations
“…6-8 emu ml −1 ) is not observable by the XMCD technique owing to the small magnitude of the moment. Our work has shown that this enhanced magnetic moment in the highly strained Rphase disappears around 150 • C; further, application of an electric field converts this mixed phase into the T-phase, and the enhanced magnetic moment disappears; reversal of the field brings the mixed phase back accompanied by the magnetic moment in the distorted R-phase [20]. These observations raise several questions: first, what is the magnetic state of the strained R-phase?…”
Section: Phase Control Through Epitaxial Constraintsmentioning
confidence: 85%